2021
DOI: 10.3390/en14113087
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Interactions between Injection Events Using Multiple Injection Strategies and a Solenoid Diesel Injector

Abstract: An experimental study was performed to explore the influence of dwell time on the hydraulic interactions between injection events using pilot injection strategy, split injection strategy, post injection strategy and a solenoid diesel injector. To do so, a sweep of dwell time from 0.55 up to 2 ms using all multiple injection strategies and levels of rail pressure, of 80, 100 and 120 MPa, and single level of back pressure, of 5 MPa, was performed. The hydraulic interactions between injection events were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Diesel engine still faces enormous challenges to meet the requirements of worldwide environmental problems and human health. In order to obtain better engine performance, different methods such as split injection strategy [2,3], biodiesel [4], emulsified fuels [5], and oxygen-enriched combustion [6] have been used to improve the spray breakup, combustion efficiency, and emissions. Though improved by various methods, the emission and performance of diesel engines under the sub-zero environment remains a critical problem.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engine still faces enormous challenges to meet the requirements of worldwide environmental problems and human health. In order to obtain better engine performance, different methods such as split injection strategy [2,3], biodiesel [4], emulsified fuels [5], and oxygen-enriched combustion [6] have been used to improve the spray breakup, combustion efficiency, and emissions. Though improved by various methods, the emission and performance of diesel engines under the sub-zero environment remains a critical problem.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature [8,18,32,33] The heat transfer coefficient σ was calculated with the use of equation (1) to account for the presence of a leakage flux in the magnetic circuit:…”
Section: Model Of a Solenoid Valuementioning
confidence: 99%
“…They analyzed hydraulic processes in the injector, but disregarded electromagnetic phenomena in the coil, which also play an important role in injector performance. In turn, Martínez-Martínez et al [18] analyzed the amount of injected fuel at different dwell times between injection pulses. They concluded that dwell times between successive electric pulses significantly influence the amount of delivered fuel.…”
Section: Introductionmentioning
confidence: 99%
“…When measuring the ROI, it is more accurate to reproduce as much as possible engine-like conditions (AlRamadan et al, 2019;Aljohani et al, 2019). The choice of the ROI measurement methodology is critical, particularly for multiple injection schemes (Martínez-Martínez et al, 2021). For instance, the spray momentum method could not characterize the ROI of short early injections as demonstrated in AlRamadan et al (2019).…”
Section: Introductionmentioning
confidence: 99%